BIOLOGY OF THE LARGE SNAKE-HEAD OPHICEPHALUS MARULWS; (HAM.) IN BHAVANISAGAR WATERS - Devaraj, M (Indian Journal of Fisheries, 2011)
Lengthfrequency distribution of OpA/cepAa/(Â«warÂ«/iÂ«i(Hani.)fromPoongar Swamp dissected out by probability plot technique produced fouryear classes, von Bertalanffy’s growth equation adequately describes the growth of O. marulius. The mean length at first maturity is 460 mm in females and 550 miu in males. The Im/Loo value for the former is 0.41 and for the latter 0.45. A rapid fall in fecundity is observed in olderfishes (4 year and above). Peak spawning occurs during November and December in the swamp but during June and July in theriver and reservoir. Parental care ceases when the young ones are 4-month old. Fish less than 50mm long feed on zooplankton especially Dapfiniabni those 50 to 110mm long prey upon Macrohrachium and larger insect nymphs